Learning Curve for a Dual Attending Surgeon Strategy in Posterior Spinal Fusion (PSF): An Analysis of 105 Severe Adolescent Idiopathic Scoliosis Patients (Cobb Angle ≥90°). Issue 12 (15th June 2021) - Chan, Chris Yin Wei; Lee, Sin Ying; Ch'ng, Pei Ying; Chung, Weng Hong; Chiu, Chee Kidd; Hasan, Mohd Shahnaz; Kwan, Mun Keong
Abstract : Study Design: Retrospective study. Objective: To assess the learning curve of a dual attending surgeon strategy in severe adolescent idiopathic scoliosis patients. Summary of Background Data: The advantages of a dual attending surgeon strategy in improving the perioperative outcome in scoliosis surgery had been reported. However, the learning curve of this strategy in severe scoliosis had not been widely studied. Methods: A total of 105 patients with adolescent idiopathic scoliosis with Cobb angle of 90° or greater, who underwent posterior spinal fusion using a dual attending surgeon strategy were recruited. Primary outcomes were operative time, total blood loss, allogeneic blood transfusion requirement, length of hospital stay from time of operation and perioperative complications. Cases were sorted chronologically into group 1: cases 1 to 35, group 2: cases 36 to 70, and group 3: case 71 to 105. Mean operative time ( ⩽ 193.3 min), total blood loss (⩽1612.2 mL), combination of both and allogeneic blood transfusion were the selected criteria for receiver operating characteristic analysis of the learning curve. Results: The mean Cobb angle was 104.5° ± 12.3°. The operative time, total blood loss, and allogeneic blood transfusion requirement reduced significantly for group 1 (220.6 ± 54.8 min; 2011.3 ± 881.8 mL; 12 cases) versus group 2 (183.6 ± 36.7 min; 1481.6 ± 1035.5 mL; 3 cases) and group 1 versus group 3 (175.6 ± 38.4 min; 1343.7 ± 477.8 mL; 3 cases) ( P < 0.05). There were six perioperative complications. Fifty-seven cases were required to achieve the preset criteria (mean operative time and mean total blood loss) (area under the curve 0.740; P < 0.001; sensitivity 0.675; specificity 0.662). Conclusion: There was significant improvement in operative time and total blood loss when comparing group 1 versus group 2 and group 1 versus group 3. The cut-off point for the learning curve was 57 cases when the preset criteria were fulfilled ( ⩽ 193.3 min operative time and ⩽ 1612.2 mL of total blood loss ) . Level of Evidence: 4 Abstract : This study analyzed the learning curve of a dual attending surgeon strategy for 105 severe scoliosis patients (≥90°) in terms of their perioperative outcomes. Operative time, total blood loss, and allogeneic blood transfusion requirement reduced significantly over time without reaching a plateau.